Prolapse surgery with or without incontinence procedure: a systematic review and meta‐analysis. (13th November 2017) - van der Ploeg, JM; van der Steen, A; Zwolsman, S; van der Vaart, CH; Roovers, JPWR
Abstract : Background: To reduce the risk of postoperative stress urinary incontinence (POSUI) prolapse repair might be combined with incontinence surgery. Objectives: Compare efficacy and safety of prolapse surgery with and without incontinence surgery. Search strategy: Including our earlier review a systematic search in PubMed, EMBASE, the Cochrane Library and the Register of Current Controlled Trials was performed from 1995 to 2017. Selection criteria: Randomised trials comparing prolapse surgery with a midurethral sling (MUS) or Burch colposuspension. Data collection and analysis: Two reviewers selected eligible articles and extracted data. Stress urinary outcomes were pooled for preoperative SUI. Urgency incontinence and adverse events were pooled for incontinence procedure. Main results: Ten trials were included. Women with preoperative SUI symptoms or occult SUI had a lower risk to undergo subsequent incontinence surgery for POSUI after vaginal prolapse surgery with a MUS than after prolapse surgery only: 0 versus 40% [relative risk (RR) 0.0; 95% CI 0.0–0.2] and 1 versus 15% (RR 0.1; 95% CI 0.0–0.6), respectively. These differences were not significant in continent women not tested for occult SUI or without occult SUI. Serious adverse events were more frequent after vaginal prolapse repair with MUS (14 versus 8%; RR 1.7; 95% CI 1.1–2.7), but not after sacrocolpopexy with Burch colposuspension. Combination surgery did not increase the risk of overactive bladder symptoms, urgency incontinence and surgery for voiding dysfunction. Conclusions: Vaginal prolapse repair with MUS reduced the risk of postoperative SUI in women with preoperative SUI symptoms or occult SUI, but serious adverse events were more frequent. Tweetable abstract: Less stress incontinence after vaginal prolapse repair with sling, but more adverse events. Tweetable abstract: Less stress incontinence after vaginal prolapse repair with sling, but more adverse events.